The benefits of a prolonged-release protein substitute with similarities to natural proteins as a treatment for phenylketonuria: a plain language summary of a study in healthy adults - MacDonald, Anita; Muntau, Ania C.; Scheinin, Mika; Costantino, Niko (Informa UK Limited, 2025)
What is this summary about?: This summary describes the results of a research study that investigated the benefits of a new protein substitute, a prolonged-release amino acid mixture, used to treat people with phenylketonuria. This new mixture was compared with a standard immediate-release amino acid mixture to examine amino acid absorption. The study included 35 healthy adults without phenylketonuria. What did the researchers find?: The peak amounts of amino acids in the blood were lower and the amino acids remained in the blood for longer after the prolonged-release mixture compared with the immediate-release mixture. The overall amounts of amino acids in the blood during the study were similar with both products. The difference between the amounts of nitrogen taken up and removed from the body (which is called the ‘nitrogen balance’), as well as the pattern of glucose and insulin levels in the blood, were better after the prolonged-release mixture. There were very few side effects when either of the amino acid mixtures was taken. What do the results of the study mean?: The prolonged-release and immediate-release amino acid mixtures did not differ in terms of the overall amounts of amino acids they released into the body, but they did differ in the benefits they provided, including a more natural pattern of amino acid absorption (similar to protein eaten from food), which results in the more effective use of amino acids by the body, with the prolonged-release mixture. Clinical Trial Registration: ISRCTN11016729 (ClinicalTrials.gov).